Novel protection method for VSC‐HVDC transmission lines. Issue 16 (18th December 2018) - Jiang, Lingtong; Chen, Qing; Wang, Lei; Zhao, Pu; Zeng, Yu; Huang, Wudi
Abstract : The large shunt capacitances on both sides of VSC‐HVDC transmission line will block and reflect the travelling waves when a fault occurs on DC cable lines. When a forward fault occurs, the protection will detect the arrival of forward and backward travelling wave simultaneously. While for a backward fault, the arrival time difference of the forward and backward travelling wave head is obvious. According to this characteristic, this paper proposed a novel VSC‐HVDC directional pilot protection based on the propagation time difference of directional travelling wave and the stationary wavelet transform (SWT) is used to identify the initial travelling wave head. A two‐terminal VSC‐HVDC system is modelled in PSCAD/EMTDC, and various faults scenarios are simulated to verify the proposed method. The simulation results show that the proposed protection can identify internal faults from external faults quickly and reliably, and it is basically immune to fault resistance and fault distance, which has certain practical value.